Optimal Disassembly System Design with Environmental and Economic Parts Selection for CO2 Saving Rate and Recycling Cost - Igarashi, Kento; Yamada, Tetsuo; Itsubo, Norihiro; Inoue, Masato (International Journal of Supply Chain Management, 2014)
For promoting material circulation by recycling and preventing global warming caused by CO2 emissions simultaneously, it is essential for recycling factories of end-of-life assembly products to economically disassemble and recover the parts/materials with higher CO2 volumes which can save the CO2 emissions comparing to produce the same virgin parts/materials.This paper proposes a disassembly system design with an optimal environmental and economic parts selection which harmonizes a CO2 saving rate and recycling cost using a Life Cycle Inventory (LCI) database. The first stage is to optimize the environmental and economic parts selection by the integer programming with ε constraint, and the second stage is to carry out the disassembly line balancing for minimizing the number of stations.